1957
DOI: 10.1152/ajplegacy.1957.188.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Urea Excretion in the Camel

Abstract: The mean transport number for AGh in aqueous solution was found to be 0.22 (S.E. = 0.015, n = 27). The variability arising from different sources during the iontophoretie application of drugs was estimated. The estimates were used to obtain the distribution of quantities of AGh likely to be released by particular values of electrical charge. The distributions illustrated that considerable differences are likely to exist between quantities of AGh delivered from different electrodes by the same charge. UREA GONS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…While Schmidt-Nielsen et al (1957) found that almost all of the urea injected into the camel on a low nitrogen intake was retained, the output of urinary nitrogen in the sheep under discussion was a reflection of both the total nitrogen intake and the urea nitrogen injected into the blood. Nevertheless, under conditions where an economy of nitrogen was important to the sheep.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While Schmidt-Nielsen et al (1957) found that almost all of the urea injected into the camel on a low nitrogen intake was retained, the output of urinary nitrogen in the sheep under discussion was a reflection of both the total nitrogen intake and the urea nitrogen injected into the blood. Nevertheless, under conditions where an economy of nitrogen was important to the sheep.…”
Section: Discussionmentioning
confidence: 90%
“…Schmidt- Nielsen et al (1957) found that when the need for protein was high, such as in periods of rapid growth, or when the protein intake was low, the camel can conserve nitrogen by reducing the urinary excretion of urea to extremely low levels. The same workers sliowed that urea injected intravenously during periods of low nitrogen intake was not excreted in the urine, but was retained.…”
Section: Introductionmentioning
confidence: 99%
“…The urinary urea concentration exceeds the maximal urea concentration in the papilla, consistent with passive urea reabsorption (1)(2)(3). Low protein diets change inner medullary urea handling in the rat (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), sheep (13)(14)(15)(16)(17), camel (18), and man (19). In rats fed a low protein diet, fractional excretion of urea is significantly reduced compared to rats fed normal or high protein diets, consistent with stimulation ofurea reabsorption by protein restriction (1,5,8,10,12).…”
Section: Introductionmentioning
confidence: 82%
“…Dans In ruminants, endogenous urea reaches the The hydrolysis of endogenous urea in the digestive tract in the saliva (Bailey and gastrointestinal tract has been studied in Balch 196 la,b; Somers l96la,b,c,d), monogastic animals (Walser and Bodenlos through the rumen epithelium (Houpt 1959;t959;McKinley et al 1970;Prior et al Juhasz 1965;Packett and Groves 1965;, and in ruminants (Ford and Milligan Cosimano and Leng 1967;Weston and 19'/0;Leng 1970, 1972; Hogan 196l; Houpt and Houpt 1968; Mugerwa and Conrad 197 l; Robbins et al Vercoe 1969), and through the wall of the 1974). Schmidt-Nielsen et al (1957) flushing of the needle with saline. At 2-h h. The reaction was terminated by injecting I ml intervals for the first 12 h after injection and at of 1.5 N perchloric acid into the reaction 4-h intervals for the next 40 h, l0-ml blood chamber, and the flasks were shaken for I h to samples were collected into heparinized tubes.…”
mentioning
confidence: 99%